Development of Task-Based Textbooks Incorporating Local Wisdom to Improve Writing Skills Among Junior High School Students in Bantul Regency - Nina Widyaningsih; Yanuar Bagas Arwansyah; Bayu Ananto Wibowo (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study was prompted by the low level of student engagement in writing lessons at lower secondary school, particularly when teaching procedural texts, which are still dominated by lecture-based methods, the use of generic teaching materials, and a lack of integration of local cultural contexts into the learning process. These conditions result in students being less active, easily bored, and struggling to express their ideas coherently in writing. This study aims to develop a task-based textbook incorporating local wisdom to improve the writing skills of junior high school students in Bantul Regency. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the analysis, design, development, implementation, and evaluation stages. The research was conducted at State Junior High School 2 Imogiri, with the test subjects comprising Year 7 pupils, Indonesian language teachers, subject matter experts, and experts in teaching materials or media. Data collection methods included observation, interviews, questionnaires, tests and documentation. The data were analysed using both qualitative and quantitative methods. The research findings indicate that the textbook developed meets the criteria for suitability based on expert validation, is practical based on feedback from teachers and pupils, and is effective for use in teaching procedural writing. The use of a task-based approach helps pupils to write in a gradual and structured manner, whilst the inclusion of local wisdom makes learning more contextual, closely aligned with pupils’ experiences, and encourages greater engagement in the learning process. Consequently, task-based textbooks incorporating local wisdom can be used as an alternative teaching resource in Indonesian language lessons to support the development of pupils’ writing skills.